Heterozygosity for cervid S138N polymorphism results in subclinical CWD in gene-targeted mice and progressive inhibition of prion conversion - Arifin, Maria I.; Kaczmarczyk, Lech; Zeng, Doris; Hannaoui, Samia; Lee, Chi; Chang, Sheng Chun; Mitchell, Gordon; McKenzie, Debbie; Beekes, Michael; Jackson, Walker; Gilch, Sabine (Proceedings of the National Academy of Sciences, 2023)
Prions are proteinaceous infectious particles that replicate by structural conversion of the host-encoded cellular prion protein (PrPC), causing fatal neurodegenerative diseases in mammals. Species-specific amino acid substitutions (AAS) arising from single nucleotide polymorphisms within the prion protein gene (Prnp) modulate prion disease patho-genesis, and, in several instances, reduce susceptibility of homo-or heterozygous AAS carriers to prion infection. However, a mechanistic understanding of their protective effects against clinical disease is missing. We generated gene-targeted mouse infection models of chronic wasting disease (CWD), a highly contagious prion disease of cervids. These mice express wild-type deer or PrPC harboring the S138N substitution homo-or heterozygously, a polymorphism found exclusively in reindeer (Rangifer tarandus spp.) and fallow deer (Dama dama). The wild-type deer PrP-expressing model recapitulated CWD pathogenesis including fecal shedding. Encoding at least one 138N allele pre-vented clinical CWD, accumulation of protease-resistant PrP (PrPres) and abnormal PrP deposits in the brain tissue. However, prion seeding activity was detected in spleens, brains, and feces of these mice, suggesting subclinical infection accompanied by prion shedding. 138N-PrPC was less efficiently converted to PrPres in vitro than wild-type deer (138SS) PrPC. Heterozygous coexpression of wild-type deer and 138N-PrPC resulted in dominant-negative inhibition and progressively diminished prion conversion over serial rounds of protein misfolding cyclic amplification. Our study indicates that heterozy-gosity at a polymorphic Prnp codon can confer the highest protection against clinical CWD and highlights the potential role of subclinical carriers in CWD transmission. Funding Agencies|Natural Sciences and Engineering Research Council; Margaret Gunn Endowment for Animal Research; Parks Canada Agency; Genome Canada; Canada Research Chair program